Quantifying the Impact of Nanoparticle Coatings and Non-uniformities on XPS Analysis: Gold/silver Core-shell Nanoparticles - Wang, Yung-Cheng (Anal Chem, 2016)
Spectral modeling of photoelectrons can serve as a valuable tool when combined with X-ray photoelectron spectroscopy (XPS) analysis. Herein, a new version of the NIST Simulation of Electron Spectra for Surface Analysis (SESSA 2.0) software, capable of directly simulating spherical multilayer NPs, was applied to model citrate stabilized Au/Ag-core/shell nanoparticles (NPs). The NPs were characterized using XPS and scanning transmission electron microscopy (STEM) to determine the composition and morphology of the NPs. The Au/Ag-core/shell NPs were observed to be polydispersed in size, non-spherical, and contain off-centered Au-cores. Using the average NP dimensions determined from STEM analysis, SESSA spectral modeling indicated that washed Au/Ag-core shell NPs were stabilized with a 0.8 nm layer of sodium citrate and a 0.05 nm (one wash) or 0.025nm (two wash) layer of adventitious hydrocarbon, but didn’t fully account for the observed XPS signal from the Au core. This was addressed by a series of simulations and normalizations to account for contributions of NP non-sphericity and off-centered Au-cores. Both of these non-uniformities reduce the effective Ag-shell thickness, which effect the Au-core photoelectron intensity. The off-centered cores had the greatest impact for the particles in this study. When the contributions from the geometrical non-uniformities are included in the simulations, the SESSA generated elemental compositions that matched the XPS elemental compositions. This work demonstrates how spectral modeling software such as SESSA, when combined with experimental XPS and STEM measurements, advances the ability to quantitatively assess overlayer thicknesses for multilayer core-shell NPs and deal with complex, nonideal geometrical properties.